Fascicles split or merge every ∼560 microns within the human cervical vagus nerve - Upadhye, Aniruddha R; Kolluru, Chaitanya; Druschel, Lindsey; Al Lababidi, Luna; Ahmad, Sami S; Menendez, Dhariyat M; Buyukcelik, Ozge N; Settell, Megan L; Blanz, Stephan L; Jenkins, Michael W; Wilson, David L; Zhang, Jing; et al. (Journal of neural engineering, 2022)
Vagus nerve stimulation (VNS) is Food and Drug Administration-approved for epilepsy, depression, and obesity, and stroke rehabilitation; however, the morphological anatomy of the vagus nerve targeted by stimulatation is poorly understood. Here, we used microCT to quantify the fascicular structure and neuroanatomy of human cervical vagus nerves (cVNs). We collected eight mid-cVN specimens from five fixed cadavers (three left nerves, five right nerves). Analysis focused on the 'surgical window': 5 cm of length, centered around the VNS implant location. Tissue was stained with osmium tetroxide, embedded in paraffin, and imaged on a microCT scanner. We visualized and quantified the merging and splitting of fascicles, and report a morphometric analysis of fascicles: count, diameter, and area. In our sample of human cVNs, a fascicle split or merge event was observed every ∼560 m (17.8 ± 6.1 events cm ). Mean morphological outcomes included: fascicle count (6.6 ± 2.8 fascicles; range 1-15), fascicle diameter (514 ± 142 m; range 147-1360 m), and total cross-sectional fascicular area (1.32 ± 0.41 mm ; range 0.58-2.27 mm). The high degree of fascicular splitting and merging, along with wide range in key fascicular morphological parameters across humans may help to explain the clinical heterogeneity in patient responses to VNS. These data will enable modeling and experimental efforts to determine the clinical effect size of such variation. These data will also enable efforts to design improved VNS electrodes.